2018
DOI: 10.1016/j.placenta.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated placental microRNAs in Early and Late onset Preeclampsia

Abstract: Since specific miRNAs can differentiate EOPE and LOPE from uncomplicated placentas, they may be considered as putative PE-specific biomarkers. MiR-518a-5p emerged as a potential diagnostic indicator for EOPE cases as well as for PE-FGR complicated placentas, indicating a potential link to the severity of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 41 publications
1
38
0
Order By: Relevance
“…However, there are few relevant studies on this miRNA. It has been revealed that dysregulated expression of miR-431 relates to the occurrence of preeclampsia [12], diffuse large B-cell lymphoma [13] and hepatocellular carcinoma [13, 14], among other conditions. However, the significance of miR-431 in lung development, including its regulation of pulmonary surfactant, has been poorly explored.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few relevant studies on this miRNA. It has been revealed that dysregulated expression of miR-431 relates to the occurrence of preeclampsia [12], diffuse large B-cell lymphoma [13] and hepatocellular carcinoma [13, 14], among other conditions. However, the significance of miR-431 in lung development, including its regulation of pulmonary surfactant, has been poorly explored.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are known to play a critical role in the pathogenesis of PCOS and pregnancy-related disorders 45 47 . Pathways such as adipocytokine signaling, oxytocin signaling, TNF signaling, progesterone-mediated oocyte maturation, estrogen signaling, MAPK, and FoxO signaling are known to be regulated by miRNAs and associated with pregnancy outcome 48 , 49 .…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, miRNA deep sequencing in first trimester maternal plasma samples was performed to identify candidate biomarkers associated with the subsequent development of LOPE and provide useful insights regarding pathways associated with the initiation and the development of this pregnancy related complication. In a previous study, we documented differential expression of placental and circulating miRNAs in PE highlighting a significant role of this epigenetic mechanism in the pathogenesis of the complication (18). That study was performed in placenta samples, thus limiting its potential use in prenatal screening.…”
Section: Discussionmentioning
confidence: 99%